Mobile-app-based assistant for freshmen with telegram APIs - Foo, Kai Lin (Nanyang Technological University, 2021)
In this project, the development of the Telegram-based chatbot, “Hey! NTU” bot, aims to provide readily available online support and resource for NTU freshmen. Apart from guiding freshmen to essential and relevant information with its Natural Language Processing (NLP) query response capabilities, the chatbot also allows students to plan and check their academic schedules so that they do not forget any important events. Other useful tools that make daily school life easier are incorporated to provide further assistance. These tools include a to-do list, a calculator, and a timer function. When chatting with the bot, students can expect conventional replies like how a conversation would flow. This all-in-one interactive chatbot helps make freshmen’s transition to NTU smooth sailing.